Gamification and Robotics in STEAM Education: A Case Study in Rural Areas of Arequipa and Huancayo: Integrating Lunabot for Technological Advancement and Iterative Design in Robotics Learning - Juan Diego Cerrón Salcedo; Jair Jesús León Lucano; Alberto Torres Hinostroza; Joaquin De los Rios Rosado; Klinge Villalba Condori (Interaction Design and Architecture(s))
This study presents a case study on the application of gamified educational practices in STEAM education, specifically focusing on the use of robotics and iterative design among youth in rural areas of Arequipa, Peru. The study involved the integration of “Lunabot,” an educational robot, to foster technological advancement and enhance learning experiences. Conducted in the “tambos” (rural community centers) of the Arequipa region, the research employed a mixed-methods approach, combining quantitative and qualitative data collection methods. Initially, an exploratory factor analysis was conducted to condense the data, followed by a confirmatory factor analysis through structural equation modeling to validate the findings. A key instrument was a questionnaire administered to students, assessing their interest in, and resistance to, the gamified learning approach. The results, with a Cronbach’s alpha value of 0.765 and a McDonald’s omega of 0.864, highlight the significant role of competitive and challenging activities, facilitated by Lunabot, in enhancing student engagement and motivation in gamification and STEAM learning. This case study contributes to understanding how gamified strategies and robotics can be effectively integrated into educational settings, particularly in remote areas, to improve student participation and motivation in STEAM fields.